Bone histology of the Middle Triassic long-necked reptiles Tanystropheus and Macrocnemus (Archosauromorpha, Protorosauria). Issue 2 (4th March 2017) - Jaquier, Vivien P.; Scheyer, Torsten M.
SUPPLEMENTAL DATA: Supplemental materials are available for this article for free at www.tandfonline.com/UJVP Citation for this article: Jaquier, V. P., and T. M. Scheyer. 2017. Bone histology of the Middle Triassic long-necked reptiles Tanystropheus and Macrocnemus (Archosauromorpha, Protorosauria). Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1296456.